Hidden caries: a critical review - Trevisan, Tamara Carolina [UNESP]; Andrade, Maria Costa de [UNESP]; Presoto, Cristina Dupim [UNESP]; Oliveira Júnior, Osmir Batista de [UNESP]; Andrade, Marcelo Ferrarezi [UNESP; Bortolatto, Janaína Freitas [UNESP] (Incessant Nature Science Publishers, 2015)
Hidden caries is a type of lesion visualized in dentin, mainly by means of bitewing radiographs, in which, clinically, the occlusal enamel appears healthy or minimally demineralized and radiographically presents progressive demineralization in dentin, which may progress and compromise the pulp-dentin complex. Although the etiology of hidden caries is unknown, many theories have been studied, including structural and anatomical defects of enamel, their specific microbiota and the use of fluoride, which is most accepted theory. Considering the clinical concern, since these lesions have a silent progression and often are not detected on routine clinical examinations, this study aims to conduct a critical discussion of the etiology, prevalence, diagnostic methods and treatment decision for lesions of hidden caries, alerting professionals about the importance of routine use of bitewing radiographs even in patients considered “cariesfree” or low risk of caries, for more effective diagnosis.